Maternal characteristic and perinatal outcomes among peruvian women infected with COVID-19. An observational and cross-sectional study - Huatuco-Hernández, Jorge A. (2021)
Objetive: To determine the maternal characteristics of women infected with COVID-19 and their neonates born in the COVID-19 referral hospital (HRDT) between April and September 2020. Material and Methods: Observational and cross-sectional study carried out in the HRDT that included 703 obstetric patients with COVID-19. Results: The average age was 27 years. 35.7% were nulliparous and 95% were asymptomatic for COVID-19. 3%, 1% and 1% had mild, moderate and severe COVID-19; respectively. The most frequent symptoms were cough (84.85%) and anosmia (39.39%). The most common signs were tachypnea (60.61%) and respiratory distress (51.52%). Blood gas, D-dimer, and ferritin were altered in 71%, 54%, and 30%; respectively. The most frequent medical complications were: sepsis (2.28%), pneumonia (2.13%), respiratory failure (2.13%) and septic shock (1.14%). The most frequent obstetric complications were premature rupture of membranes (6.69%), severe preeclampsia (5.41%), abortive syndrome (3.27%) and preterm labor (2.56%). 73.9% of deliveries were by Caesarean section. 0.99% of patients required intensive care unit and maternal mortality was 0. 2%. 85.7% of neonates were at term and 97.2% had APGAR ≥7 at 5 minutes. There were 4 neonatal deaths (0.64%) and 16 deaths (2,58%). There were 8 positive RT-PCR in neonates (1.3%). Conclusion: The majority of patients were nulliparous, under 35 years of age and asymptomatic for COVID-19. Most of the newborns were born by cesarean section and evolved favorably. There were two maternal deaths, 16 stillbirths, and 4 neonatal deaths.